Trickle-Down Economics Arthur Lewis dan Ekonomi Pembangunan Wisata Gunung Bromo di Desa Ngadisari, Kabupaten Probolinggo, Jawa Timur Tahun 2017-2018 - Puspitarini, Renny Candradewi; Anggraini, Isrofiatul (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
In this paper, we will examine if trickle-down effect has ever taken in rural Indonesia. One of the case draws attention in economic development study is poverty and income gap from wealthiest people to the less fortunate larger group of people. The argument goes as trickle-down effect appears to be best solution to eradicate poverty as well as to solve the income gap. Tourism has become of a strategy targeted by government to spread the trickle-down effect to the less fortunate larger group of people. Government believes by sustaining the growth on tourism would accelerate the trickle-down effect and brings less fortunate group of people to better living. In its fundamental theory, trickle- down effect has offered delusion where jobs would be created as the conditions are met. However, this paper argues that even in tourism the trickle-down effect strategy has served less for what it has promised. Through qualitative research in Ngadisari Village, a remote area, where Mount Bromo has been a tourism landmark globally, this paper finds that trickle-down effect has come with little benefit to uplift the living standard of the poor. Thus, trickle- down effect has served only as delusions of growth government has ever aspired.